ηQ Meson Photoproduction in Ultrarelativistic Heavy Ion Collisions - Gong-Ming Yu; Gao-Gao Zhao; Zhen Bai; Yan-Bing Cai; Hai-Tao Yang; Jian-Song Wang (Advances in High Energy Physics)
The transverse momentum distributions for inclusive ηc,b meson described by gluon-gluon interactions from photoproduction processes in relativistic heavy ion collisions are calculated. We considered the color-singlet (CS) and color-octet (CO) components within the framework of Nonrelativistic Quantum Chromodynamics (NRQCD) in the production of heavy quarkonium. The phenomenological values of the matrix elements for the color-singlet and color-octet components give the main contribution to the production of heavy quarkonium from the gluon-gluon interaction caused by the emission of additional gluon in the initial state. The numerical results indicate that the contribution of photoproduction processes cannot be negligible for midrapidity in p-p and Pb-Pb collisions at the Large Hadron Collider (LHC) energies.